2022
DOI: 10.1037/tmb0000068
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of five key perceptual cues and their interaction to the sense of embodiment.

Abstract: A range of perceptual cues drive the Sense of Embodiment (SoE) with an external object, such as a virtual arm that looks like one's own or can be controlled like one's own. Since most experiments test one or two cues at a time, it is difficult to establish their relative contribution and possible interaction. This work aims at investigating the importance of five key perceptual cues (field of view, visuo-proprioceptive synchronicity, tactile feedback, visual human likeness, and connectedness) and their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…However, the SoE factors cannot be regarded isolated from each other, as interrelations were identified [36], such as appearance influences on agency [37], and control/haptics on ownership [38][39][40]. Here, recent findings showed that primarily visuo-proprioceptive congruence contributes to the sense of agency and ownership, as well as a better task performance [28]. Moreover, Fribourg et al (2020) explored the user preferences for three vital factors (i.e.…”
Section: Immersion Into Ivr Avatars For Ivbomentioning
confidence: 98%
See 2 more Smart Citations
“…However, the SoE factors cannot be regarded isolated from each other, as interrelations were identified [36], such as appearance influences on agency [37], and control/haptics on ownership [38][39][40]. Here, recent findings showed that primarily visuo-proprioceptive congruence contributes to the sense of agency and ownership, as well as a better task performance [28]. Moreover, Fribourg et al (2020) explored the user preferences for three vital factors (i.e.…”
Section: Immersion Into Ivr Avatars For Ivbomentioning
confidence: 98%
“…For instance, an egocentric POV has been shown to reliably induce the sense of self-location [23], while a third-person perspective tends to lower it [24,25]. The sense of agency is induced through the experienced control toward the virtual body [15], influenced by the visuomotor congruence between real body and avatar [26][27][28], while incongruences tend to lower it [29,30]. Lastly, the sense of ownership is influenced by the body appearance and has been induced through avatar models with different degrees of anthropomorphism [31].…”
Section: Immersion Into Ivr Avatars For Ivbomentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, an egocentric POV has been shown to reliably induce the sense of self-location [27], whereas a third-person perspective tends to lower it [28,29]. The sense of agency is induced through the experienced control of the virtual body [19], influenced by the visuomotor congruence between the real body and avatar [30][31][32], whereas incongruences tend to lower it [33,34]. Finally, the sense of ownership is influenced by body appearance and has been induced through avatar models with different degrees of anthropomorphism [35].…”
Section: Immersion Into Ivr Avatars For Ivbomentioning
confidence: 99%
“…However, the SoE factors cannot be considered to be isolated from each other, as interrelations have been identified [ 40 ], such as influence of appearance on agency [ 41 ] and control and haptics on ownership [ 42 - 44 ]. Here, recent findings showed that primarily visuoproprioceptive congruence contributes to the sense of agency and ownership and better task performance [ 32 ]. Moreover, Fribourg et al [ 40 ] explored the user preferences for 3 vital factors (ie, POV, control, and appearance), showing the need for an egocentric perspective and high motor control to outweigh the avatar’s appearance.…”
Section: Introductionmentioning
confidence: 99%